(untitled) (Revista da Tulha, 2016)
This paper investigates the Dandô Project — Dércio Marques Music Circuit, attempting to understand its meanings, as well as the role of the Viola Caipira in this context. The text discusses authors such as Geertz (2012), Merriam (1964), Seeger (2008), Blacking (1974), Cambria (2015), Titon (2016), Vilela (2013), Brandão (2005, 2008, 2009), among others. Through an ethnographic study of two concerts within the Dandô Project, in Brasília, it was verified that the songs performed, as well as the instrumental performances themselves, convey a discourse related to the defense of popular culture and of the environment. This interconnection between music and nature refers us to the field of Ecomusicology, which may offer new approaches to tackle old problems of music and culture through studies that are connected with environmental concerns.